2014
DOI: 10.1890/es14-00139.1
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar diversity as a means of ecologically intensifying dry matter production in a perennial forage stand

Abstract: Abstract. The relationship between genotypic diversity and productivity has not been adequately explored in perennial forage production systems despite strong theoretical and empirical evidence supporting diversity's role in ecosystem functioning in other managed and unmanaged systems. We conducted a two-year field experiment with six cultivars of an agriculturally important forage grass, Lolium perenne L. (perennial ryegrass). Dry matter production of L. perenne and the weed community that emerged from the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…However, increased homogeneity at the landscape scale confers a greater risk of pathogen and pest infestations (Gustafson et al 2003, Robertson et al 2008, Hartman et al 2011). This suggests that the inclusion of undomesticated strains in switchgrass biomass plantings may increase site-level yield, as was found for mixtures of switchgrass cultivars (Morris et al 2016) and perennial ryegrass (Lolium perenne; Pollnac et al 2014). Additionally, we found that, at each site, particular undomesticated populations produced more biomass than particular cultivars even though cultivars as a group were more productive.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, increased homogeneity at the landscape scale confers a greater risk of pathogen and pest infestations (Gustafson et al 2003, Robertson et al 2008, Hartman et al 2011). This suggests that the inclusion of undomesticated strains in switchgrass biomass plantings may increase site-level yield, as was found for mixtures of switchgrass cultivars (Morris et al 2016) and perennial ryegrass (Lolium perenne; Pollnac et al 2014). Additionally, we found that, at each site, particular undomesticated populations produced more biomass than particular cultivars even though cultivars as a group were more productive.…”
Section: Discussionsupporting
confidence: 72%
“…Additionally, we found that, at each site, particular undomesticated populations produced more biomass than particular cultivars even though cultivars as a group were more productive. This suggests that the inclusion of undomesticated strains in switchgrass biomass plantings may increase site-level yield, as was found for mixtures of switchgrass cultivars (Morris et al 2016) and perennial ryegrass (Lolium perenne; Pollnac et al 2014).…”
Section: Discussionmentioning
confidence: 64%
“…Legume persistence in mixed swards could be enhanced by selecting legume species and cultivars with proven persistence abilities for the local environment and that have good competitive abilities, and by matching legumes with grasses that are less aggressive in competition (Annicchiarico & Proietti ). Genotypic diversity has successfully increased yields of L. perenne (Pollnac, Smith & Warren ) suggesting that enhancing functional trait diversity by combining mixtures of cultivars with mixtures of species may lead to additional diversity effects to ecosystem function than mixing species alone. Further research is needed to explore this.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is disagreement in the literature about the impacts of genetic management on yield increases. While some authors argue that crop and cultivar diversity is positively and significantly related to production [120][121][122], others maintain that a productivity increase is observable only in normal years, not during extreme weather events or epidemics [123]. Notably, most of the research documenting the benefits of diversification evaluated a single ecosystem service [124].…”
Section: Genetic Managementmentioning
confidence: 99%